Coupled plasma transport and electromagnetic wave simulation of an ECR thruster. (8th April 2021) - Sánchez-Villar, Álvaro; Zhou, Jiewei; Ahedo, Eduardo; Merino, Mario
Abstract: An electron-cyclotron resonance thruster (ECRT) prototype is simulated numerically, using two coupled models: a hybrid particle-in-cell/fluid model for the integration of the plasma transport and a frequency-domain full-wave finite-element model for the computation of the fast electromagnetic (EM) fields. The quasi-stationary plasma response, fast EM fields, power deposition, particle and energy fluxes to the walls, and thruster performance figures at the nominal operating point are discussed, showing good agreement with the available experimental data. The ECRT plasma discharge contains multiple EM field propagation/evanescence regimes that depend on the plasma density and applied magnetic field that determine the flow and absorption of power in the device. The power absorption is found to be mainly driven by radial fast electric fields at the electron-cyclotron resonance region, and specifically close to the inner rod. Large cross-field electron temperature gradients are observed, with maxima close to the inner rod. This, in turn, results in large localized particle and energy fluxes to this component.